Primary presentation and clinical course of pediatric and adolescent patients with differentiated thyroid carcinoma after radioiodine therapy - Caroline Burgard; Caroline Burgard; Mathias Johannes Zacherl; Mathias Johannes Zacherl; Andrei Todica; Andrei Todica; Julia Hornung; Freba Grawe; Freba Grawe; Isabell Pekrul; Petra Zimmermann; Petra Zimmermann; et al. (Frontiers in Oncology, 2023)
IntroductionDifferentiated thyroid carcinoma (DTC) in childhood and during adolescence is extremely rare. Pediatric DTC commonly presents with advanced disease at diagnosis including a high prevalence of cervical lymph node metastases and pulmonary metastases. Studies in children with DTC are limited. Therefore, we aimed to evaluate the initial presentation, effectiveness of radioiodine therapy (RIT), and long-term outcome of prepubertal in comparison to pubertal/postpubertal patients.MethodsEighty-five pediatric and young patients aged 6.4 to 21.9 years with histopathologically confirmed DTC were retrospectively included. They all underwent total thyroidectomy followed by RIT. Initial presentation and outcome of prepubertal and pubertal/postpubertal patients were compared 1 year after RIT, during follow-up, and at the last visit of follow-up.ResultsPrepubertal patients presented with significantly higher T and M stages. One year after RIT, 42/81 (52%) patients still presented with evidence of disease (ED). During follow-up of a median of 7.9 years, prepubertal patients were less often in complete remission (58% vs. 82% in pubertal patients). At the last visit of follow-up, 19/80 (24%) patients still had ED without statistical differences between the two groups (42% prepubertal vs. 18% pubertal/postpubertal, p-value 0.06). None of our patients died disease-related over the observed period.ConclusionPrepubertal children with DTC presented with a more advanced tumor stage at the initial presentation. During follow-up, they present more often with ED. However, at the end of our study, we did not observe statistically relevant differences in patient outcomes between the prepubertal and pubertal/postpubertal groups.